Differential Expression of lncRNAs and miRNAs Between Self-Rooting Juvenile and Donor Clones Unveils Novel Insight Into the Molecular Regulation of Rubber Biosynthesis in Hevea brasiliensis - Li, Hui-Liang; Wang, Ying; Guo, Dong; Zhu, Jia-Hong; Peng, Shi-Qing (Frontiers in Plant Science, 2022)
The rubber tree (Hevea brasiliensis Muell. Arg.) is a tropical tree species that produces natural rubber. Self-rooted juvenile clones (SRJCs) are novel rubber tree planting materials developed through primary somatic embryogenesis. SRJCs have a higher rubber yield compared with donor clones (DCs). The molecular basis underlying increased rubber yield in SRJCs remains largely unknown. Here, the latex from SRJCs and DCs were collected for strand-specific and small RNA-seq methods. A total of 196 differentially expressed long noncoding RNAs (DELs) and 11 differentially expressed microRNAs were identified in latex between SRJCs and DCs. Targeted genes of DELs were markedly enriched for various biological pathways related to plant hormone signal transduction, photosynthesis, glutathione metabolism, and amino acids biosynthesis. DELs probably acted as cis-acting regulation was calculated, and these DELs relevant to potentially regulate rubber biosynthesis, reactive oxygen species metabolism, and epigenetic modification. Furthermore, the DELs acting as microRNA targets were studied. The interaction of microRNA and DELs might involve in the regulation of natural rubber biosynthesis.